Persepsi Mahasiswa Mengenai Pelaksanaan Layanan Pendidikan Mata Kuliah Pendidikan Agama Islam di FMIPA Unikaltar Tahun Akademik 2021/2022 - Abdul Arif; Ratna Dwi Christyanti (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The Faculty of Mathematics and Natural Sciences (FMIPA) of the University of East Kalimantan (Unikaltar) consistently conducts satisfaction surveys to improve the quality of services provided to students. This survey aims to evaluate the performance of each work unit, including lecturers, with the hope that the results obtained can identify aspects that are still hampering or suboptimal. The survey results serve as the basis for formulating steps to improve and enhance the quality of educational services within the faculty. This study specifically highlights the level of student satisfaction with the performance of lecturers in the Islamic Religious Education course. The survey implementation process includes several stages, starting from data collection using a survey instrument, the data input process, and testing the validity and reliability of the instrument to ensure data reliability. Next, the collected data is processed and analyzed to obtain an objective picture of student perceptions. Based on the analysis, the student satisfaction index value obtained is 3.16. This figure is in the